Spatial cognition X : 13th Biennial Conference, KogWis 2016, Bremen, Germany, September 26-30, 2016, and 10th International Conference, Spatial Cognition 2016, Philadelphia, PA, USA, August 2-5, 2016, Revised selected papers /: 13th Biennial Conference, KogWis 2016, Bremen, Germany, September 26-30, 2016, and 10th International Conference, Spatial Cognition 2016, Philadelphia, PA, USA, August 2-5, 2016, Revised selected papers. (2017) - Unknown
No abstract available